Energetic Microparticle Adhesion to Functionalized Surfaces. Issue 9 (2nd August 2018) - Hoss, Darby J.; Mukherjee, Sanjoy; Boudouris, Bryan W.; Beaudoin, Stephen P.
Abstract: Surface chemistry influences interfacial interactions, and while these interactions have been evaluated in many synthetic and biological systems, they have important but unexplored implications in trace explosives detection. Specifically, the detection of energetic materials is a challenging, urgent goal, and one of the most common means by which this effort is implemented at air transportation checkpoints is using methods based on contact sampling. Elucidating the molecular and interfacial interactions of energetic materials with functionalized surfaces provides fundamental knowledge and also advances the goal of improved materials for trace detection. Here, in order to evaluate the effects of specific functional groups on adhesion, atomic force microscopy (AFM) pull‐off force measurements were performed using nitrate‐based energetic (and non‐energetic) particles against self‐assembled monolayers (SAMs) of representative chemical functionalities. These SAMs‐on‐gold substrates were selected to evaluate surface chemistry effects due to their reproducibility, facile production, and versatile tunability. In addition to the experimental results, stabilization energies for the optimized most‐stable configurations for a coupled receptor‐analyte system were determined using density functional theory (DFT). From these combined experimental and computational efforts, it is established that the adhesion between detection surfaces and common energetic materials at the macroscopic scales is correlated to the interaction energies at the molecular level. Moreover, the electron deficient nature of nitro‐rich energetic compounds results in stronger interactions with surfaces functionalized with electron‐donating units. Ultimately, these results will facilitate the rational design of energetic particle collection materials through chemical tailoring in order to enhance the detection and defeat of explosive materials. Abstract :